(untitled) (Journal of the Management Sciences, 2025)
Health literacy is a potent factor that determines several health-related variables including reproductive health. The study assessed health literacy and its relationship with reproductive health behaviour among female staff at the University of Ibadan, Nigeria. The cross-sectional study was performed in 2024 on 185 female staff of the University of Ibadan aged between 19 to 49 years who had been selected through a stratified and random sampling technique from among those with the criteria for entering the study. Two adapted instruments labelled Health Literacy (α=0.79) and Reproductive Health Behaviour Questionnaires (α=0.81) were used for data collection and analysed using frequency counts, percentages and Pearson Product Moment Correlation at a significant level of less than 0.05. The study found that the average mean health literacy of female employees at the University was high (x ̅=3.89., there is a significant relationship between health literacy and reproductive health behaviour among female staff at the University(r=.504 p<0.05). According to the correlation analysis, the number of children (r = .439, p< .05), income status (r = .630, p< .05), age (r = .633, p< .05), educational attainment (r = .648, p< .05), job description (r = .657, p< .05), were found to be predictors of health literacy, respectively. Female staff at the university have high health literacy and exhibit good reproductive health practices. Therefore, enlightenment programmes regarding good reproductive health practices should be made readily available at University Health Services, health information on reproductive health must be provided on various platforms accessible to all female staff and factors such as age, educational level, income, number of children and job description should be considered when planning initiatives to increase health literacy in women.